ANTIMICROBIAL SENSITIVITY PATTERN OF PEDIATRIC CYSTIC FIBROSIS PATIENTS IN PAKISTAN - ULLAH , G; AHSAN , F; FARRUKH , S; QAISRANI , MA; YASIN , M; AKHTAR , M (Biological and Clinical Sciences Research Journal, 2023)
Cystic fibrosis (CF) is a complex genetic disorder affecting the respiratory and digestive systems, causing recurrent infections. This study aimed to evaluate the microbiological cultures and identify the patterns of antimicrobial sensitivity among young CF patients in Pakistan. This prospective observational study was conducted at the Pakistan Institute of Medical Sciences (PIMS) from December 2021 to November 2022, involving comprehensive assessments, interviews, clinical tests, MTs, CBCs, CXRs, sputum cultures, RBS measurements, microbiological analysis of sputum and oropharyngeal swabs, antimicrobial susceptibility testing, and statistical analyses (p ≤ 0.05) using SPSS for both continuous and categorized data. Pseudomonas Aeruginosa was the most common respiratory pathogen (n=21; 36%), and most CF-afflicted children (n=46; 77.96%) had infections with a single microorganism. Significant associations (p < 0.05) were observed between Streptococcus pneumoniae, Klebsiella Pneumoniae, Staphylococcus Aureus, and Acinetobacter with their antibiotic sensitivity patterns. In contrast, Pseudomonas Aeruginosa and Escherichia Coli showed no statistically significant associations. Ciprofloxacin demonstrated high sensitivity, followed by Levofloxacin, while several first-generation antibiotics, including rifampicin, erythromycin, and amoxicillin, exhibited nearly complete resistance against bacteria collected from children with CF. Ciprofloxacin and Levofloxacin emerge as the foremost effective therapeutic agents for CF patients, advocating the perpetual promotion of active surveillance to monitor resistance patterns.